The end of the Asian century war, stagnation, and the risks to the world's most dynamic region - Auslin, Michael R. (Yale University Press, 2017)
Historian and geopolitical expert Michael Auslin argues that far from being a cohesive powerhouse, Asia is a fractured region threatened by stagnation and instability.